ANALISIS PENAWARAN DAN PERMINTAAN LADA INDONESIA DI PASAR INTERNASIONAL - SABARMAN DAMANIK (Pusat Penelitian dan Pengembangan Perkebunan, 2001)
Analysis of Indonesian pepper supply and demand in the International MarketStudy on the supply and demand of Indonesian pepper in the international market was conducted by using the data of time series from 1980 to 1999. The data were analyzed using multiple linear regression and two stage least square (2 SLS) estimation method. The result of analysis revealed that the factors affecting pepper supply from Indonesia were international market, world price, pepper production, exchange rate, and the last export volume. The supply export of pepper of each major pepper producing counlircs showed similar characeristics, i.e. die expot of pepper of the countries, including Indonesia was affeclcd signiicantly by the national pepper production. When the price changed, the supply would change with the percentage higher than that of the price change. The demand for pepper import at the elasticity coeicient value smaller than one (0.144 -0.680) meant that it was inelastic. The elasticity coeficient value of the Indonesian pepper supply in the short and long terms was 1 168 and 4.037 respectively. It meant that they were elastic, if the price changed, the supply would change with the percentage higher than thai of the price change. The implication to Ihe pepper industry in Indonesia were (a) the decrease in Ihe pepper price in the international market did not affect the national pepper production, and (b) the exchange rale affect the volume of the pepper export.